2018
DOI: 10.1093/dote/doy053
|View full text |Cite
|
Sign up to set email alerts
|

Lower prevalence of gastroesophageal reflux disease in patients with noncardiac chest pain on opiates: a cross-sectional study

Abstract: Opiates can cause heartburn and spastic esophageal dysmotility but their role in noncardiac chest pain (NCCP) is not known. Our aim was to characterize opiate effects on esophageal function using esophageal pH monitoring and high-resolution manometry (HREM) in these patients.We performed a cross sectional study of opiate users with NCCP who underwent HREM and esophageal pH study from 2010 to 2017 using opiate nonusers as a comparison group. Demographic data, symptoms, opiate use, endoscopic findings, esophagea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…A total of 621 publications were identified in the initial search, of which 376 were excluded as duplicates (see Supplementary Figure 1, http://links.lww.com/AJG/C999). After applying these exclusion criteria, a total of 9 full articles involving 10,292 patients (1,749 opioid users and 8,543 nonopioid users) were included in the meta-analysis (4–9,15–17). Most of the included studies were conducted in the United States (n = 8), and one was conducted in Switzerland.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 621 publications were identified in the initial search, of which 376 were excluded as duplicates (see Supplementary Figure 1, http://links.lww.com/AJG/C999). After applying these exclusion criteria, a total of 9 full articles involving 10,292 patients (1,749 opioid users and 8,543 nonopioid users) were included in the meta-analysis (4–9,15–17). Most of the included studies were conducted in the United States (n = 8), and one was conducted in Switzerland.…”
Section: Resultsmentioning
confidence: 99%
“…To determine the effect of opioid use on EGJOO, a meta-analysis was conducted on 8 studies comprising 1,711 opioid users and 8,201 nonopioid users (4–9,15,16). The results showed a significant increase in the risk of EGJOO in opioid users compared with nonopioid users (pooled OR 5.13, 95% CI 2.11–12.43, P = 0.0003, I 2 = 93%) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Cifuentes et al (19), evaluated patients with non cardiac chest pain taking opioids that underwent HRM and ambulatory pH monitor testing, noteworthy; they found that opioid consumption is associated with a significantly lower esophageal total acid exposure. They attribute this finding to a higher LES resting pressure, which reduces reflux episodes, and a greater DCI that may enhance esophageal acid clearance mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…5 Consequently, opioid medications can result in both obstructive (i.e., dysphagia) and perceptive (i.e., heartburn, chest pain) esophageal symptoms. 6 Functional lumen imaging probe (FLIP) adapts impedance planimetry to provide real-time cross-sectional area and bolus transit information in response to volumetric balloon distension during sedated upper endoscopy. 7 Abnormal esophagogastric junction (EGJ) opening can be characterized based on EGJ diameter and distensibility index (DI).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic use of opioid medications potentiates pain transmission pathways, leading to accentuation of perceptive sensations including esophageal pain 5 . Consequently, opioid medications can result in both obstructive (i.e., dysphagia) and perceptive (i.e., heartburn, chest pain) esophageal symptoms 6 …”
Section: Introductionmentioning
confidence: 99%